Investigating the performance parameters of solar cell for efficiency enhancement - Muhammad Muneeb Khan; Sadiq Ahmad; Jahangeer Faiz; Rubab Nazeer; Muhammad Amir Shafi; Ahmad Bin Ishtiaq (Mehran University Research Journal of Engineering and Technology)
Copper Zinc Tin Selenide (CuZnTSe) cells have unique physical characteristics that make them incredibly well-suited to serve as a solar material for power absorption in contemporary optimized Thin Film Solar cells (TFSC). The goal of the proposed study is to model novel hetero-structures for CuZnTSe solar cells with and without a NiO hole transport layer (HTL), namely AlZno2/Cds/CuZnTSe/Mb and Al-Zno2/Cds/CuZnTSe/Nio2/Mb. To develop and simulate the properties of the CuZnTSe cell and its possible applications in photovoltaic solar cells, simulation software SCAPS-1D is utilized. In addition to nickel oxide (NiO) serving as the electron-blocking HTL, transparent conductor oxide films such as aluminum zinc oxide (AlZnO) and cadmium sulfide (Cds) were added as electron transport layers. The incorporation of a NiO hole transport layer, carrier concentration, layer thickness, defect density, and other parameters impacting cell efficiency were all examined in this work. For the configurations under analysis, the maximum power efficiencies were 23.09% and 39.54%, respectively, with top fill-factors exceeding 79.47% and 87.21%.